Proximal femoral nail anti-rotation versus cementless bipolar hemiarthroplasty for unstable femoral intertrochanteric fracture in the elderly: a retrospective study - Zhou, Shenghu (BMC Musculoskelet Disord, 2019)
BACKGROUND: The treatment for unstable intertrochanteric fractures in the elderly has always been a controversial issue. The aim in this study was to compare the curative effects of proximal femoral nail anti-rotation (PFNA) and cementless bipolar hemiarthroplasty (CPH) on femoral intertrochanteric fracture in the elderly. METHODS: From March 2008 to December 2012, 108 elderly patients with femoral intertrochanteric fractures were treated by PFNA or CPH. There were 63 males and 45 females, aged 75.3–99.1 years [(83.7 ± 5.6) years]. The patients’ bone mineral density was routinely measured, and the fractures were classified according to Evans-Jensen. The patients were divided into CPH group and PFNA group. The differences in operation time, intraoperative bleeding, immobilization duration, hospitalization time, Harris scores and postoperative complications including deep venous thrombosis, lung and urinary infection were analyzed. RESULTS: All patients were followed for 12.5–36.2 months [(28.0 ± 6.3) months)]. The operation time was (53.7 ± 15.2) min and (77.5 ± 16.8) min in PFNA group and CPH group, respectively (P < 0.05); intraoperative bleeding was (132.5 ± 33.2) mL and (286.3 ± 43.2) mL, respectively (P < 0.05); immobilization duration was (28.2 ± 3.7) days and (3.1 ± 1.2) days, respectively (P < 0.05); hospitalization time was (7.6 ± 1.8) days and (6.9 ± 2.2) days, respectively (P > 0.05); and the Harris scores after 1 year were (87.7 ± 7.9) points and (88.3 ± 9.2) points, respectively (P > 0.05). There was no significant difference in postoperative complications between the two groups (P > 0.05). CONCLUSION: Both PFNA and CPH are safe and effective treatments for femoral intertrochanteric fracture in elderly patients. Nonetheless, CPH allows faster mobilization and recovery. TRIAL REGISTRATION: Registration Number: ChiCTR1900022846. Reg Date:2019-04-26 00:27:33 Retrospective registration